The effects of decolonial praxis on leaders of transformative movements: The case of Masivule in South Africa - Sekowe, Cliff; Okyere Asante, Michael K.; van den Brink, Jessica; Andrason, Alexander (Critical Studies in Teaching and Learning, 2025)
While the effects experienced by the leaders of radical transformative movements at universities in South Africa and other countries have become evident over the last decades, the scholarly discussion and theorisation thereof, especially by those directly involved in these movements, has been scarce. This article addresses this knowledge gap and discusses the consequences suffered by the leaders of a small, albeit no less radically transformative, movement that took place at a middle-size department at a historically white South African university in 2022: #Masivule_i-Antieke_Studies. By exploring an auto-ethnographic method and couching their personal experiences within decolonial theory, the authors – who were among the six Masivule founders and activists – conclude that: contesting (post-/epi-)colonial powers at universities has both negative and positive effects on the architects/leaders of decolonial movements, which are visible in four domains: structural, epistemic, personal, and relational. While structural, epistemic, and relational effects gradually become mostly positive, personal effects remain profoundly (albeit not exclusively) negative. The authors propose that the most promising or effective way to deal with traumatic experiences and render them generative is to embrace decoloniality – not only as a method of transforming a particular department, university, or field, but as a philosophy governing one’s professional career and life.